Saint Christopher (West Indies)
Articles of surrender as outlined by the British for the French withdrawal from the island of Saint Christopher (Saint Kitts).
Collection material in French, with marginal notes in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: France -- Colonies -- America; Great Britain -- Colonies -- America; Saint Kitts -- History